2008
DOI: 10.1017/s0033822200033555
|View full text |Cite
|
Sign up to set email alerts
|

AMS Dating on the Shell Bar Section from Qaidam Basin, Ne Tibetan Plateau, China

Abstract: ABSTRACT. Radiocarbon dating by accelerator mass spectrometry (AMS) of the shell bar section of Qaidam Basin, NE Tibetan Plateau, shows that this section was formed between ~39.7 and ~17.5 14 C kyr BP and represented the highest paleolake development period since the Late Pleistocene. It was difficult to obtain reliable dates due to the low organic carbon content, which was formed mainly by authochtonous algae-bacteria (Zhang et al. 2007a). In order to improve the dating, 14 C ages of both the alkali residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…The detailed dating study can be found in refs. [33,34]. For the sake of comparison, we use the online radiocarbon calibration program provided by University of Cologne (http://www.calpal-online.de) to calibrate the 14 C age data.…”
Section: Sampling and Experimental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed dating study can be found in refs. [33,34]. For the sake of comparison, we use the online radiocarbon calibration program provided by University of Cologne (http://www.calpal-online.de) to calibrate the 14 C age data.…”
Section: Sampling and Experimental Analysismentioning
confidence: 99%
“…CPI h =oddΣ[C[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] ]/evenΣ [C[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36];ACL h =(Σ[C i ] ×i)/Σ[C i ] (22≤i≤37); P aq =(C 23 +C 25 )/(C 23 +C 25 +C 29 +C 31 ).…”
mentioning
confidence: 99%
“…Based on a detailed comparison and discussion on dating results, we identified the "true ages" from the "sample ages" and established the chronology of the Shell Bar section using the "true ages". These dates suggest that the studied section was formed between 39.7 (the bottom of the lacustrine deposits) and 17.5 14 C ka BP [7,10] . In addition the 14 C dates were calibrated to calendar years using the on-line program via website http://www.calpal-online.de.…”
Section: Sampling and Chronologymentioning
confidence: 99%
“…Alloying Mg with Ca increases the strength and corrosion resistance [7], while the presence of Zn in the binary Mg-Ca alloys enhances the precipitation hardening response [8], and Mn addition can improve the strength of Mg alloy effectively through grain refinement [9]. Recently, Mg-Zn-Ca alloys with high hardness and good creep resistance have been developed, due to the existence of fine stable precipitates in the alloys [10,11], which are considered as Ca 2 Mg6Zn3 [11,12].…”
Section: Introductionmentioning
confidence: 99%